HER2/neu Expression in Gastrointestinal Carcinoma Among South Indians - Priyadharshini, Gayathri; Mahesh, Kiran Chokka; Ramdas, Anita; Varghese, Renu G’Boy (Annals of Pathology and Laboratory Medicine, 2020)
Background: HER2/neu oncogene overexpression and amplification in breast cancer is well known. Studies have proved its role in gastric cancer and its correlation with the prognosis. Very few studies are there in literature regarding HER2/neu expression in entire gastrointestinal carcinoma. Our study was aimed at HER2/neu expression in gastrointestinal tumors in South Indian Population. M ethods: We included all patients with gastrointestinal carcinoma who either underwent biopsy or surgical excision over the past five years. Slides were reviewed for confirmation of the diagnosis and immunohistochemistry was done using SP3 monoclonal anti-HER2 antibodies. Three independent observers did the scoring for HER2 positivity. Results: Among 35 cases of gastric cancer, only 2 (5.7%) females showed positivity for HER2 scoring and one (2.9%) female showed an equivocal result. All positive and equivocal cases in gastric cancer were intestinal type. Both the cases with HER2 positivity were poorly differentiated tumors. The one with equivocal was a moderately differentiated carcinoma. In colorectal cancer out of 19 cases, only one (5.3%) showed positivity for HER2 whereas in one there was an equivocal response. All the seven cases of small intestinal carcinoma showed negative results for HER2 expression. Conclusion: Overall, HER2/neu expression in gastrointestinal cancer was 4.9%. Female gender, intestinal- type and poorly differentiated cancer showed positivity in gastric cancer. Female gender, left side and low-grade tumor showed positivity in colorectal cancer. Further studies are required with a large sample size to correlate HER2 expression with clinicopathological parameters and its role in prognosis in gastrointestinal carcinomas in the Indian population.